ANALISIS PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN HARGA POKOK PRODUKSI KAIN BATIK TULIS (STUDI PADA PERUSAHAAN BATIK MARELY JAYA) - Alfian Helmy; Novi Darmayanti; Nurul Fauziyah (LPPM UNISDA, 2019)
This research to analyze calculation the cost of good manufactured is activity based costing system. This method is able to provide the cost of good manufactured calculations is precise and accurate compared with the traditional system. The purpose of this research was to find out how the application of traditional systems and activity based costing system to determine the cost of good manufactured batik cloth at Merely Jaya Batik Company, and to determine whether There is a difference in the calculation of the cost of batik cloth between traditional systems and activity based costing system. The type of this research is descriptive quantitative.